Physical activity level among women: Promoting sports and exercises across demographic determinants / Marwa Abd Malek and Mawarni Mohamed - Abd Malek, Marwa; Mohamed, Mawarni (Penerbit UiTM (UiTM Press), 2017)
The top ten killer diseases in Malaysia are largely associated with inactivity. In relation to that, Malaysia has come out with policies on prevention, control and management of non-communicable diseases (NCD) into the social, economic and environmental systems through various stakeholders. Thus, this study examined the level of physical activity (PA) among women with regards to demographic profiles, namely marital status, occupation, academic qualification and BMI. A sample of 390 women in Selangor was randomly selected. This research employed a quantitative method using a set of questionnaire adapted from International Physical Activity Questionnaire (IPAQ) in order to obtain information from the respondents. Then, descriptive analysis was employed to obtain the frequency and percentage of PA level. ANOVA was also used to find out the difference in PA with regards to demographic profiles. This study revealed that women in Selangor were generally at low level of PA. In terms of marital status, single women were moderately participated in PA as compared to married and divorced women who participated in low PA. In terms of occupation, home maker, self-employed, white-collar and students participated moderately in PA. On the other hand, professionals and unemployed women participated in low PA. It was also found that school leavers and women with certificate participated at moderate level of PA, yet, women with degree and above as well as diploma were doing low PA. Women with extra body weight, normal body weight and less body weight were found to participate at high, moderate and low level of PA respectively. Besides, findings proved that academic qualification and BMI were highly associated with PA participation. However, marital status and occupation did not associate with PA participation.